2017
DOI: 10.4000/rccs.6797
|View full text |Cite
|
Sign up to set email alerts
|

Deve a economia feminista ser pós-colonial? Colonialidade económica, género e epistemologias do Sul

Abstract: Neste artigo analiso o fenómeno da colonialidade económica, observando os seus impactos no tecido social e o modo como atinge particularmente a vida das mulheres – nomeadamente as subalternas, estejam elas nas periferias das grandes cidades do mundo ou constituam minorias numéricas ou simbólicas no Sul ou Norte globais. Interessa-me verificar de que modo as colonialidades económica e de género interagem, acentuando a situação de desigualdade em que se encontram estas mulheres. Por fim, indago em que medida as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to Ramos (1989), the substantive organization always seeks in society the support for its actions, in the context of the SFEN, this support is sought especially at the local level, through the voluntary actions that women perform with the community, which are processes of learning that also emancipate women, as they make them be seen outside their homes. According to Santos (2017) and Bauhardt (2014), the feminist economy is a perspective of analysis of the field of economic sciences that incorporates gender relations in the understanding of economic thought, in this sense, the movement seeks to transform socioeconomic relations, aiming at a new form of work organization and a new society, based on the recognition and equal conditions for women. However, women's perception of the recognition they receive from actions taken is critical; for them, there is a mix of recognition and non-recognition, which is expressed in different ways.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ramos (1989), the substantive organization always seeks in society the support for its actions, in the context of the SFEN, this support is sought especially at the local level, through the voluntary actions that women perform with the community, which are processes of learning that also emancipate women, as they make them be seen outside their homes. According to Santos (2017) and Bauhardt (2014), the feminist economy is a perspective of analysis of the field of economic sciences that incorporates gender relations in the understanding of economic thought, in this sense, the movement seeks to transform socioeconomic relations, aiming at a new form of work organization and a new society, based on the recognition and equal conditions for women. However, women's perception of the recognition they receive from actions taken is critical; for them, there is a mix of recognition and non-recognition, which is expressed in different ways.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…From this influx of studies related to SE, research is identified that analyze the factors that guided the rise of SE enterprises (Borzaga and Tortia, 2007;Singer, 2008;Gaiger, 2011), studies that observe SE as a social movement of nature popular (Arruda, 2008;Costa, 2011;Singer, 2008), checks on the impacts of enterprises on local economies (França Filho, 2013;Oliveira, 2005), studies that observe labor relations in the context of SE (Guérin, 2003;Hirata 2002;Holzmann, 2002;Oliveira, 2008;Segnini, 2003;Silva, 2012), research on public policies within the scope of SE (Dagnino, 2011;Gaiger, 2011;Monje-Reyes, 2011), studies on dilemmas of Solidarity Economy (Barreto and Paula, 2009;Onuma, Mafra and Moreira, 2012;Sá and Soares, 2005), analyzes on the formation of cooperation networks between enterprises (Mance, 2006;Scherer-Warren, 2012;Soares et al , 2016), studies that question the capacity of SE as an alternative observing o the limits placed by the market system (Bauhardt, 2014;Costa, 2011, Pinheiro andPaula, 2014), research on organizational dynam-ics in the scope of ES enterprises (Costa & Carrion, 2009;Faria, 2017;França Filho, 2013;Pinheiro e Paula, 2014;Santos, 2017;Silva, 2018), among others.…”
Section: Introductionmentioning
confidence: 99%